2012
DOI: 10.1155/2012/549241
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationships between Lipid Metabolism and Liver Regeneration

Abstract: The regenerative capacity of the liver is well known, and the mechanisms that regulate this process have been extensively studied using experimental model systems including surgical resection and hepatotoxin exposure. The response to primary mitogens has also been used to investigate the regulation of hepatocellular proliferation. Such analyses have identified many specific cytokines and growth factors, intracellular signaling events, and transcription factors that are regulated during and necessary for normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
113
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 89 publications
13
113
0
Order By: Relevance
“…The most important source of lipids that accumulates in the regenerating liver is mainly free fatty acids supplied from adipose tissue. However, de novo hepatic fatty acid synthesis has also been reported (26). According to these observations, our study shows a delay in fat accumulation that is accompanied by a delay in cell proliferation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The most important source of lipids that accumulates in the regenerating liver is mainly free fatty acids supplied from adipose tissue. However, de novo hepatic fatty acid synthesis has also been reported (26). According to these observations, our study shows a delay in fat accumulation that is accompanied by a delay in cell proliferation.…”
Section: Discussionsupporting
confidence: 75%
“…H&E-stained sections show no major abnormalities in the livers of SULF2-KO compared with WT mice at baseline. Microvesicular steatosis, a well-known histopathological feature present during regeneration after PH (22)(23)(24)(25)(26)(27), was seen in both WT and SULF2-KO mouse livers beginning at 12 h after PH. However, 48 h after PH, SULF2-KO mice showed a decrease in microvesicular steatosis compared with WT mice.…”
Section: Loss Of Sulf2 Delays Liver Regenerationmentioning
confidence: 99%
“…For example, supplemental glucose affects patterns of histone acetylation in cell culture, [24][25][26] PH-induced hypoglycemia occurs during experimental liver regeneration, and glucose supplementation inhibits regeneration. 7,23,27 In addition, HDAC5 undergoes PH-induced nuclear localization in regenerating liver, 2 and this Zn-HDAC also exhibits hypoglycemia-induced nuclear localization and regulates FOXO target gene expression in other models. 28 Finally, recent studies suggest that specific metabolites modulate isoformspecific HDAC activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Strey et al demonstrated that IL-6-STAT3 pathway played key roles in regulating liver proliferation mediated by C3a and C5a (14). Liver proliferation is an energy and material-consuming process that causes a dramatic consuming of both TG and cholesterol from serum and liver in a short time (15). Although the detailed lipid regulatory pathway is still unclear, lots of studies have reached a consensus on the lipid metabolic characteristics during this process (15)(16)(17)(18)(19).…”
Section: Ivyspringmentioning
confidence: 99%
“…Liver proliferation is an energy and material-consuming process that causes a dramatic consuming of both TG and cholesterol from serum and liver in a short time (15). Although the detailed lipid regulatory pathway is still unclear, lots of studies have reached a consensus on the lipid metabolic characteristics during this process (15)(16)(17)(18)(19). It enhanced fatty acid oxidation in liver for energy production, and upregulated both hepatic cholesterol synthesis and uptake for cell membrane synthesis (15,16).…”
Section: Ivyspringmentioning
confidence: 99%